Seasonal influence of the surgical outcome after thoracic sympathectomy for hyperhidrosis - Lima, Alexandre Garcia de [UNESP]; Milanez de Campos, Jose Ribas [UNESP]; Jatene, Fabio Biscegli [UNESP] (Springer, 2011)
Analyze the seasonal variation of the surgical results after sympathectomy through the seasons of the year. The surgical results are better in the spring, and the sudomotor reflex is worst in summer. Comparison of surgical results of distinct techniques should be done under the same climatic conditions.
Keywords: Hyperhidrosis; Sympathectomy; Sympathectomy/adverse effects; Seasonal variations